Arabic Curriculum Planning Management - Muhammad Ridha Assagaf (Golden Ratio of Data in Summary, 2024)
This study aims to explore the management of Arabic curriculum planning in Indonesian higher education, focusing on the effectiveness of planning in addressing challenges in teaching and learning Arabic. Utilizing a qualitative approach and library research methods, the study analyzes literature related to curriculum management and its implementation at three higher education institutions. The findings reveal that the curriculum planning process involves stages of needs analysis, goal formulation, content development, teaching strategies, and evaluation, although the depth and approach vary between institutions. The study identifies that while the integration of technology into the curriculum has begun, the level of implementation differs. Multicultural aspects and labor market orientation are also focal points, with results showing that while some institutions have integrated modules for business and diplomatic Arabic, multicultural aspects remain limited. These findings underscore the need for a more holistic curriculum planning approach that is responsive to digital advancements and sensitive to cultural diversity and labor market needs. The study recommends developing a comprehensive curriculum management model to enhance the relevance and effectiveness of Arabic language learning in Indonesia.